ANALISIS BIAYA PRODUKSI PUPUK KOMPOS DALAM MENINGKATKAN LABA BERSIH PADA KELOMPOK USAHA BERSAMA (KUB) MATTIROWALIE DESA TOLOWE PONRE WARU, KEC. WOLO, KAB. KOLAKA - Arnianti, Iin; Sabarudin, Sabarudin; Bustang, Bustang (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the production costs of compost fertilizer in an effort to increase net profit at the Mattirowalie Joint Business Group (KUB), Tolowe Ponre Waru Village, Wolo District, Kolaka Regency. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The informants in this study were the owners of the Mattirowalie KUB business. The data used consisted of primary data obtained through interviews, as well as secondary data in the form of business financial reports. The results of the study showed that production costs consisted of raw material costs, operational costs, and manufacturing costs, which were analyzed manually. Net profit growth has increased significantly, namely by 50.40% in 2023 and increasing again to 92.46% in 2024. The strategies implemented to increase net profit include increasing sales, improving product quality, production cost efficiency, reducing unnecessary operational costs, optimizing the production process, and developing partnerships with suppliers and distributors. Keywords: Production Cost, Compost Fertilizer , Net Profit